Increased Circulating Malondialdehyde-Modified Low-Density Lipoprotein Level Is Associated with High-Risk Plaque in Coronary Computed Tomography Angiography in Patients Receiving Statin Therapy - Ichikawa, Keishi (J Clin Med, 2021)
Objective: To evaluate the association of serum malondialdehyde low-density lipoprotein (MDA-LDL), an oxidatively modified LDL, with the prevalence of high-risk plaques (HRP) determined with coronary computed tomography angiography (CTA) in statin-treated patients. Methods: This study was a single-center retrospective cohort comprising 268 patients (mean age 67 years, 58% men) with statin therapy and who underwent coronary CTA for suspected stable coronary artery disease. Patients were classified into two groups according to median MDA-LDL level or median LDL-C level. Coronary CTA-verified HRP was defined when two or more characteristics, including positive remodeling, low-density plaques, and spotty calcification, were present. Results: Patients with HRP had higher MDA-LDL (p = 0.011), but not LDL-C (p = 0.867) than those without HRP. High MDA-LDL was independently associated with HRP (odds ratio 1.883, 95% confidential interval 1.082–3.279) after adjustment for traditional risk factors. Regarding incremental value of MDA-LDL for predicting CTA-verified HRP, addition of serum MDA-LDL levels to the baseline model significantly increased global chi-square score from 26.1 to 32.8 (p = 0.010). Conclusions: A high serum MDA-LDL level is an independent predictor of CTA-verified HRP, which can lead to cardiovascular events in statin-treated patients.